IMPLEMENTASI KARTU UNIVERSAL MEDICAL IDENTITY (UMI) TERHADAP WAKTU PROSES IDENTIFIKASI DATA SOSIAL PASIEN DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN DI RSUD BANGIL TAHUN 2016 - Dewi H.S., Endang Sri; Gunawan, Gunawan; Erawati, Nur (DINAMIKA DOTCOM, 2019)
The first time patient visits the health care facilities is to be identified the social data of the patient. Patient registration by using the register book takes a lot of time and extend the registration process. Universal Medical Identity card (UMI) is the choice to shortening the time process of identification the social data of the patient. The aim of this research was to implement the UMI card against time identification process social data of the patient. The data obtained through observation and the time for identify the social data of patients was recorded before and after the implementation of UMI cards. Sample were the new outpatient who came to the patient regristration desk (TPPRJ) in Bangil Hospital, Pasuruan City. The statistical test using Independent t-Test proved that there was a different mean time of identification the social data of the patient before and after using the UMI card, with significancy value p < 0,05. It is suggested to use this UMI card at the patient regristration desk (TPPRJ) in Bangil Hospital, Pasuruan City, to speed up the time process of identification the social data of the patient. Key words : UMI (Universal Medical Identity ) card , time process of identification the social data of the patient